MOLECULAR DOCKING AS POTENTIAL ANTI-INFLAMMED QUERSETIN OF MORINGA LEAVES (Moringa oleifera L.) WITH AUTODOCK-VINA - Diyan, Diyan Sakti Purwanto; Hari Susanti; Nining Sugihartini (Jurnal Ilmiah Manusia Dan Kesehatan, 2021)
Inflammation is a response to tissue injury that involves a physiological process in the form of activation of the cyclooxygenase (COX) enzyme which has two isoforms, namely the cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) enzymes. The leaves of Moringa (Moringa oleifera L.) contain quercetin which has shown anti-inflammatory activity by blocking the synthesis and release of histamine and other inflammatory allergic mediators. This study aims to determine the role of quercetin in Moringa leaves as an anti-inflammatory ligand 6 COX cyclooxigenase-2 (COX-2) with the application of autodock vina. The method used was that all ligands were docking molecularly using the AutoDock Vina program. The results obtained are the binding affinity (kcal / mol) of the ligand to protein. The Ligplot + program is used to visualize the 3D conformation of molecules and ligand-protein interactions. The hardware used by ASUS notebooks with Windows 10 64 bit specifications. Based on molecular docking, quercetin has a potential activity as an anti-inflammatory because it has affinity and forms hydrogen cox 6 bonds in-silico and can be continued with in vitro activity tests in the laboratory to get results as anti-inflammatory.